Strategies for Optimizing the Soft Tissue Seal around Osseointegrated Implants. Issue 20 (27th September 2017) - Abdallah, Mohamed‐Nur; Badran, Zahi; Ciobanu, Ovidiu; Hamdan, Nader; Tamimi, Faleh
Abstract: Percutaneous and permucosal devices such as catheters, infusion pumps, orthopedic, and dental implants are commonly used in medical treatments. However, these useful devices breach the soft tissue barrier that protects the body from the outer environment, and thus increase bacterial infections resulting in morbidity and mortality. Such associated infections can be prevented if these devices are effectively integrated with the surrounding soft tissue, and thus creating a strong seal from the surrounding environment. However, so far, there are no percutaneous/permucosal medical devices able to prevent infection by achieving strong integration at the soft tissue–device interface. This review gives an insight into the current status of research into soft tissue–implant interface and the challenges associated with these interfaces. Biological soft/hard tissue interfaces may provide insights toward engineering better soft tissue interfaces around percutaneous devices. In this review, focus is put on the history and current findings as well as recent progress of the strategies aiming to develop a strong soft tissue seal around osseointegrated implants, such as orthopedic and dental implants. Abstract : Insight into the current status of research related to the integration of soft tissues around implants inserted through the human skin and gingiva is provided in this review. Moreover, this review discusses the current findings and recent progress of the strategies aiming to establish a strong soft tissue seal around osseointegrated implants, such as orthopedic and dental implants.